Atomic structure of γ″ phase in Mg–Gd–Y–Ag alloy induced by Ag addition. Issue 16 (18th August 2019) - Sha, Xuechao; Xiao, Lirong; Chen, Xuefei; Cheng, Guangming; Yu, Yandong; Yin, Dongdi; Zhou, Hao
ABSTRACT: Mg–Gd based alloys are typical high strength magnesium alloys owing to their outstanding age hardening behavior. The mechanical strength of aged Mg–Gd alloys is enhanced by high density prismatic-shaped precipitates in Mg matrix. Moreover, the addition of Ag has been found to enhance the strength of Mg–Gd based alloys further by forming a plate-shaped precipitate, named as γ″, on basal planes of Mg. However, the structure of this precipitate is not well understood due to the complex alloying system. In this work, the atomic structure of γ″ phase is investigated using atomic-resolution high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM). Based on the accurate atomic structure from three independent directions, e.g. in [0001]Mg, [ 2 ¯ 110]Mg and [01 1 ¯ 0]Mg zone axes, the unit cell of γ″ is well established. The γ″ phase has a hexagonal structure, and its lattice parameters are a = 0.55 nm and c = 0.42 nm. The orientation relationship between γ″ phase and Mg matrix is (0001)γ″ //(0001)Mg and < 2 ¯ 110>γ″ //< 1 ¯ 010>Mg .